Pathological Changes in Intestine of Goats Naturally Affected with Cryptosporidiosis and Coccidiosis - Mishra, Vijay Kumar; Singh, Shailendra; Patel, Shailesh Kumar; Singh, Swatantra Kumar; Taibali, Sheikh (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The study was aimed to know the pathomorphological changes in intestine of goats affected with Cryptosporidium spp. and coccidian parasites. The intestinal samples from 60 slaughtered goats less than 12 months old were collected. Of these, 2 (3.33%) cases were positive for Cryptosporidium spp. infection by modified Ziehl-Neelsen staining method and 4 (6.66%) cases were positive for coccidiosis on direct faecal smear examination. Small, oval-shaped oocysts of cryptosporidium spp. were seen in intestinal contents smear. Microscopically the intestines of goats infected with Cryptosporidium spp. exhibited exfoliation and clubbing of the villi, with infiltration of mononuclear cells in the lamina propria. Several microabscesses were also observed in the jejunum and ileum. In cases positive for coccidiosis, histopathological examination revealed necrosis of the crypt epithelial lining cells, formation of crypt abscesses containing necrotic debris, and infiltration of inflammatory cells. Several developmental stages of coccidia were present within the epithelial cells of the mucosa, and lymphoid depletion was noted in the Payer’s patches of the ileocaecal region.